HUBUNGAN ANTARA KEDISIPLINAN BELAJAR DENGAN KECERDASAN LOGIS MATEMATIS SISWA DI SMP NURUL ISLAM PONTIANAK - Aprilianti, Dela (Universitas Tanjungpura, 2025)
This study aims to determine the relationship between learning discipline with logical-mathematical intelligence of students at SMP Nurul Islam Pontianak. The research method used in this study is a quantitative method in the form of correlation research. The subjects in this study were students of class VIII at SMP Nurul Islam Pontianak. The instrument used for data collection is a questionnaire about learning discipline, and a test about logical mathematical intelligence. The research was conducted by giving questionnaires about learning discipline, and test questions about logical mathematical intelligence to students. The data that has been obtained were then analyzed using prerequisite test techniques (normality and homegeneity tests) and instrument tests so that the results show that the most students learning discipline is in the high category, the most logical mathematical intelligence of students is in the low category and the relationship between learning discipline and mathematical logical intelligence is in the low category. Keywords: Intelegence, Mathematical-Logical, Study Discipline.